2021
DOI: 10.3390/ma14226880
|View full text |Cite
|
Sign up to set email alerts
|

Perinone—New Life of an Old Molecule

Abstract: A review of publications on the synthesis and properties of a family of compounds called perinones was carried out. The basic molecule has been known for several decades mainly as a photostable pigment, and in recent years it has become increasingly used in organic electronics. This paper describes the methods of synthesis of low molecular weight compounds and polymers based on that molecule; the basic spectroscopic, photochemical, electrochemical and electronic properties important for the construction of org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 176 publications
(277 reference statements)
0
3
0
Order By: Relevance
“…Tapmeyer et al and Lapkowski et al synthesised several perinone derivatives and explored their steady-state photophysical and crystallographic properties. 6,33,34 Different theoretical and experimental studies have predicted that the relationship between the stacking geometry and charge transfer dynamics in organic thin films can be controlled by tuning the electronic coupling between the molecules. [35][36][37] For instance, Castellano et al observed a red shift in the absorbance bands of perinone after substituting O with S atoms and showed the conversion of dominant singlet state fluorescence in the O substituted perinone to long-lived triplet excited states in the S substituted perinone with a lifetime of 12.9 ms. 10,30,38 Our investigation also confirms the triplet state generation with an ISC timescale of 17.58 AE 0.05 ns and 19.81 AE 0.2 ns for cis and trans perinones.…”
Section: Ta Spectroscopy Of Trans Perinone and Cis Perinone Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tapmeyer et al and Lapkowski et al synthesised several perinone derivatives and explored their steady-state photophysical and crystallographic properties. 6,33,34 Different theoretical and experimental studies have predicted that the relationship between the stacking geometry and charge transfer dynamics in organic thin films can be controlled by tuning the electronic coupling between the molecules. [35][36][37] For instance, Castellano et al observed a red shift in the absorbance bands of perinone after substituting O with S atoms and showed the conversion of dominant singlet state fluorescence in the O substituted perinone to long-lived triplet excited states in the S substituted perinone with a lifetime of 12.9 ms. 10,30,38 Our investigation also confirms the triplet state generation with an ISC timescale of 17.58 AE 0.05 ns and 19.81 AE 0.2 ns for cis and trans perinones.…”
Section: Ta Spectroscopy Of Trans Perinone and Cis Perinone Thin Filmsmentioning
confidence: 99%
“…The low-cost production, ease of molecular design, light weight, and flexibility make them promising for a variety of optoelectronic applications. [4][5][6][7] The efficiency of photovoltaic devices is related to the relative energetics of charge transfer contributor molecules. The active layer present in polymer solar cells mostly consists of a partially phase-separated blend of an electron donating conjugated semiconducting polymer and an electron accepting material, which can be small molecules, conjugated polymers, or inorganic nanocrystalline semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Naphthalene tetracarboxylic acid bisbenzimidazoles, known as perinone dyes, are a typical n-type semiconductor. [19][20][21] Perinone dyes and their derivatives have close LUMO levels to the NDI derivatives and have been successfully applied in the early bilayer heterojunction solar cells as acceptors. Because of their poor solubility in common organic solvents, perinone dyes are seldom used in the bulk heterojunction solar cells and have never been used in PSCs.…”
mentioning
confidence: 99%